Diversity in the Cow Ultralong CDR H3 Antibody Repertoire - Haakenson, Jeremy K.; Huang, Ruiqi; Smider, Vaughn V. (Frontiers in Immunology, 2018)
Typical antibodies found in humans and mice usually have short CDR H3s and generally flat binding surfaces. However, cows possess a subset of antibodies with ultralong CDR H3s that can range up to 70 amino acids and form a unique “stalk and knob” structure, with the knob protruding far out of the antibody surface, where it has the potential to bind antigens with concave epitopes. Activation-induced cytidine deaminase (AID) has a proven role in diversifying antibody repertoires in humoral immunity, and it has been found to induce somatic hypermutation in bovine immunoglobulin genes both before and after contact with antigen. Due to limited use of variable and diversity genes in the V(D)J recombination events that produce ultralong CDR H3 antibodies in cows, the diversity in the bovine antibody repertoire has been proposed to rely on AID-induced mutations, insertions and deletions targeted to the IGHD8-2 gene that encodes the entire knob region. In this review, we discuss the genetics, structure, and diversity of bovine ultralong antibodies, as well as the role of AID in creating a diverse antibody repertoire.